HPLC Quantification, Antibacterial and Antioxidant Activity of Alkaloids from Stephania glandulifera Miers - Dhungel, Jhalnath; Shyaula , Sajan L. (Journal of Institute of Science and Technology, 2025)
Stephania glandulifera Miers has been extensively used for many years as a traditional medicine; mainly roots, caudex, stem and leaves are used in the treatment of various diseases in the eastern world. This study aimed to standardize the caudex of S. glandulifera through the development and validation of a high-performance liquid chromatography method for the quantification of its major compounds. Among the five previously isolated compounds, tetrahydropalmatine (1), palmatine (2), stepholidine (4), and stepharine (5) were successfully quantified for the first time, yielding concentrations of 20.6 mg, 20.4285 mg, 19.962 mg, and 62.262 mg per gram of plant respectively. Chromatographic separation was achieved using an Agilent, Eclipse plus C18 5 µm reversed-phase column with a methanol-water gradient system with a flow rate of 1mL/ min detecting tetrahydropalmatine at 290 nm and other compounds at 190 nm. The antibacterial activity of all the four compounds along with stepharanine (3) was evaluated, with palmatine (2) showing significant efficacy against Staphylococcus aureus ATCC 25925 and vancomycin-resistant Staphylococcus aureus (MIC=0.3225 mg/mL, MBC=0.625 mg/mL). Additionally, stepharanine (3) and stepharine (5) demonstrated notable antioxidant activity (IC50=0.1384 mg/mL and 0.2944 mg/mL, respectively). These highlight stepharine, stepharanine, and palmatine as promising candidates for future drug development. Future research should explore their pharmacological potential and clinical applicability